2006
DOI: 10.1007/s10592-006-9174-1
|View full text |Cite
|
Sign up to set email alerts
|

Detecting introgressive hybridisation in rock partridge populations (Alectoris graeca) in Greece through Bayesian admixture analyses of multilocus genotypes

Abstract: The nominal subspecies of rock partridge (Alectoris graeca graeca) is widely distributed in Greece, where populations are declining due to overhunting and habitat changes. Captive-reared chukars (A. chukar) have been massively released throughout the country, raising fear that introgressive hybridisation might have disrupted local adaptations leading to further population declines. In this study we used mtDNA control-region sequences and Bayesian admixture analyses of multilocus genotypes determined at eight m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
107
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(116 citation statements)
references
References 42 publications
8
107
0
1
Order By: Relevance
“…The Bayesian clustering procedure identified seven putative introgressed individuals (6.5 % of the total sample) in comparison to 34 cases of maternal introgression (19.3 % of the total sample) directly found by discordant mtDNA and morphological traits. As previously reported by Barilani et al (2007b), the low levels of nuclear introgression (all specimens showed ^>90 %) and the presence of chukar haplotypes suggest that the admixed individuals could have had a hybrid ancestry with exotic partridges over the second past generation. In the BC subpopulation, both markers suggest the exclusion of recent admixture events with the chukar genome.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The Bayesian clustering procedure identified seven putative introgressed individuals (6.5 % of the total sample) in comparison to 34 cases of maternal introgression (19.3 % of the total sample) directly found by discordant mtDNA and morphological traits. As previously reported by Barilani et al (2007b), the low levels of nuclear introgression (all specimens showed ^>90 %) and the presence of chukar haplotypes suggest that the admixed individuals could have had a hybrid ancestry with exotic partridges over the second past generation. In the BC subpopulation, both markers suggest the exclusion of recent admixture events with the chukar genome.…”
Section: Discussionsupporting
confidence: 81%
“…If an individual did not fit this requirements, it was classified as putative hybrid. A more rigorous threshold with respect to Barilani et al (2007b) was chosen to improve the accuracy of hybrid detections (Vaha and Primmer 2006). In so doing, we used Structure to estimate the posterior probability that each individual belonged to each species or that it had fractions of its genome from two parental species.…”
Section: Laboratory Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, some uncertainty is involved in the identity of the 10 remaining individuals (Figure 2). Our simulations indicated that the identification of backcrosses is more problematic than that of F1 hybrids, because they can be confused with pure individuals and Detection of hybrids in oaks C Burgarella et al vice versa, as already shown with other hybrid systems (Barilani et al, 2007). The extent of incorrect classification can be minimized by choosing an appropriate threshold to improve accuracy (and reduce error), whereas accepting the associated trade off of loss of power (VĂ€hĂ€ and Primmer, 2006).…”
Section: Hybrid Identitysupporting
confidence: 54%
“…The risk of introgression of domestic cat genes into wildcat gene pools is a big concern to conservation biologists, since most wildcat populations are now in juxtaposition with the urban ranges of feral domestic cats (Stahl & Artois 1994). Cross-breeding with domesticated forms may culminate in the homogenization of gene pools and result in outbreeding depression, reduced fitness and, consequently, severe population declines of wild populations (Barilani et al 2007). Especially for closely related (sub)species, identifying the ecological and biological driving forces of this phenomenon can be exceptionally challenging.…”
Section: Discussion (A) Hybridization In Wildcats From Iberian Peninsulamentioning
confidence: 99%